Inventory of Land Degradation Using Geoinformatics in Cachoeiras de Macacu’s Municipality, Rio de Janeiro, Brazil - Mohammad Al Abed; Marcos Teixeira de Melo Saboya; Camila Americo dos Santos; Vania Claudia Assis; Ivandro Patrick de Oliveira Coutinho; Ruan Vargas; Fábio Ferreira Dias (Annals of Arid Zone, 2024)
This study defines the procedures applied to integrate the Geomatic techniques to characterize the spatial distribution of water erosion at Cachoeiras de Macacu, Rio de Janiro, Brazil. Different images from Landsat8, Airbus on Google Earth Pro, and drone DJI Air 2S were used to investigate the dominant erosion processes and evaluation trends, identify the various types of the stable areas, and producing the descriptive land degradation and the conservation priority maps. 841.49 km² was characterized as stable areas, while 79.46 km² was considered as unstable areas in which sheet and rill erosion remain active. Furthermore, a procedure was identified to determine the priority areas for remedial measures. A total of 81.74 km² was categorized in the priority conservation class, while 21.50 km² was classified under the high-priority class. An additional 49.26 km² fell into the unstable medium-priority class, and 10.78 km² was designated as unstable low-priority. Besides, a land-use/landcover change detection process was done to investigate those changes using Landsat images, showed a significant increase (0.76%) in urbanization, increase (1.21%) in pasture area, but 2.21% decrease in mosaic land uses. Finally, a set of remedial measures were selected to be applied in the hot spot areas.